1996
DOI: 10.1136/bjo.80.5.451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of allopurinol and steroids on inflammation and oxidative tissue damage in experimental lens induced uveitis: a biochemical and morphological study.

Abstract: BrJ Ophthalmol 1996; 80: 451-457) In direct relation to the dose administered allopurinol was shown to countercheck the oxidative tissue damage following lens induced uveitis (LIU). I This is believed to be due to its free radical scavenging activity and the scavenging of hypochlorous acid by its major metabolite oxypurinol. On the other hand, steroids applied as standard therapy for uveitis are known to reduce the synthesis of prostaglandins and thromboxanes by inhibition of the liberation of arachidonic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
1
21
0
1
Order By: Relevance
“…Doses were chosen according to the results reported by Sery and Petrillo [29], who observed very strong inflammatory reactions when using higher concentrations, and according to a preliminary series of investigations (data not shown), to obtain a mild reliable inflammatory reaction that could be followed for longer periods of time. Concentrations were also consistent with those used in previous in vitro studies [4]. Injections were realized under sterile conditions, through the pars plana, 2 mm from the limbus, with a 30-gauge needle.…”
Section: Experimental Modelsupporting
confidence: 59%
See 1 more Smart Citation
“…Doses were chosen according to the results reported by Sery and Petrillo [29], who observed very strong inflammatory reactions when using higher concentrations, and according to a preliminary series of investigations (data not shown), to obtain a mild reliable inflammatory reaction that could be followed for longer periods of time. Concentrations were also consistent with those used in previous in vitro studies [4]. Injections were realized under sterile conditions, through the pars plana, 2 mm from the limbus, with a 30-gauge needle.…”
Section: Experimental Modelsupporting
confidence: 59%
“…These pa-thologies are not well understood, but it has been clearly documented that an inflammatory reaction is involved in vitreoretinal proliferations [6,7,12,32], probably as a consequence of retinal damage and growth factor liberation. Although free radicals are not supposed to play a striking role in ocular proliferations, several studies have recently indicated that oxygen free radicals, strongly related to phagocytic and inflammatory cells, could be implicated in ocular inflammatory and proliferative disorders by way of oxidative tissue damage and lipid peroxidation [1,3,4,11,22]. In a previous study, we found that two antioxidant drugs ± EGb761 (IPSEN, France) and superoxide dismutase (SOD) ± were very efficacious in an experimental model of proliferative vitreoretinopathy based on the intravitreal injection of human platelets [8].…”
Section: Introductionmentioning
confidence: 99%
“…Schnitte (4 mm) von 3 verschiedenen Ebenen wurden mit Hämatoxilin-Eosin und nach Giemsa gefärbt. Die mikroskopische Beurteilung erfolgte durch Einteilung der Schnitte nach einem Score von 0 bis 4 entsprechend dem Grad der intraokulären Entzündung [3], die anhand der Anzahl der Entzündungszellen und des Ausmaûes der Gewebszerstörung bewertet wurde. Die Auswertung der Versuche erfolgte blind durch zwei unabhängige Untersucher und wurde 2-mal wiederholt.…”
Section: Histologische Untersuchungunclassified
“…The effects of corticosteroids are mostly because of direct action on inflammatory cells. In addition to this effect, methylprednisolone acts as a mild scavenger 79 …”
Section: Introductionmentioning
confidence: 99%